Ethosomal Drug Delivery Systems for Enhanced Topical Delivery of Antiviral and Anti-Inflammatory Drugs - Dikshita S. Sawarkar; Nitin N. Padole; Pankaj R. Dhapke; Nilakshi N. Dhoble; Jagdish R. Baheti (Asian Journal of Pharmaceutical Research and Development, 2026)
Ethosomal drug delivery systems have emerged as advanced vesicular carriers designed to enhance the topical and transdermal delivery of therapeutic agents, particularly in the management of dermatological conditions such as herpes simplex and herpes zoster. Conventional topical formulations often face significant limitations due to the barrier function of the stratum corneum, which restricts drug penetration and reduces therapeutic efficacy. To overcome these challenges, vesicular systems have been extensively explored, among which ethosomes have demonstrated notable advantages. Ethosomes are distinguished by their high ethanol content combined with flexible phospholipid bilayers, which facilitate deeper skin penetration and improved drug permeation. These systems enhance drug entrapment efficiency, increase bioavailability, and enable sustained drug release compared to traditional carriers like liposomes and niosomes. Their unique mechanism involves ethanol-induced fluidization of skin lipids along with vesicle deformability, allowing efficient transport of active compounds across skin layers. Various aspects of ethosomal systems, including their composition, classification, preparation techniques, and characterization parameters such as vesicle size, zeta potential, morphology, entrapment efficiency, in vitro release, and stability, are critical in determining their performance. Additionally, ethosomes provide a versatile platform for combination therapy by enabling co-delivery of antiviral and anti-inflammatory agents. For instance, simultaneous incorporation of drugs like acyclovir and triamcinolone acetonide offers synergistic benefits by targeting both viral replication and associated inflammation. Overall, ethosomal systems represent a promising and efficient approach for targeted and controlled topical drug delivery. Their ability to enhance permeability, improve therapeutic outcomes, and support combination therapy highlights their potential as superior alternatives to conventional formulations, paving the way for future advancements in pharmaceutical and clinical applications.